Identification of Lactic Acid Bacteria Isolate From Fermentation Food Bekasam - Ardesy Melizah; Syarif Husin; Syifa Alkaf (HM Publisher, 2018)
Bekasam is a local food from South Sumatera Indonesia, which is obtained through fermentation of fish. Previous study has shown that fermented food contained Lactic Acid Bacteria (LAB) bacteria, such as Lactobacillus plantarum, Lactobacillus sp, Pediococus sp and Weissella sp. The study was conducted to identify isolate LAB from bekasam. Bekasam contained fish, rice, and salt with a certain ratio. Further isolation of isolated LAB isolate, then performed PCR for bacterial analysis. Isolate 1 showed alleged bacteria Staphylococcus sp, non pathogen, while isolate 2 leads to Lactobacillus sp. The PCR results show the suitability of the bands formed between the Lactobacillus standard and the isolates. Keywords: bacteria, lactobacillus, acid